141 Aortic Root Replacement in Patients with Bicuspid Aortic Valve Disease Does not Increase Operative Risk – A Single Centre Experience. (3rd June 2016) - Silaschi, Miriam; Jakaj, Gentjan; Chaubey, Sanjay; Baghai, Max; Deshpande, Ranjit; John, Linday; Whitaker, Donald; Wendler, Olaf
Abstract : Objective: Bicuspid aortic valve disease (BAV) is associated with aortic root dilation (RD), increasing the risk of adverse aortic root events. Current guidelines recommend concomitant root replacement (ARR) in patients undergoing aortic valve replacement (AVR) when the root diameter (ARD) is ≥45 mm. However, ARR is believed to increase surgical risk and adherence to the guidelines is low. We reviewed current practice of surgery for BAV at our centre and compared long-term outcomes of AVR, either isolated or with ARR. Methods: Our in-hospital database was explored for patients who were treated for congenital BAV between 2004 and 2015. Patients with concomitant replacement of the ascending aorta and coronary artery bypass grafting (CABG) were left in the group, concomitant non-aortic heart valve procedures and patients with functional BAV were excluded. The remaining 242 patients were divided according to the treatment received, into patients receiving ARR (n = 59) or isolated AVR (n = 183). A sub-analysis of patients with pre-existing RD was performed. Results: ARR patients were significantly younger (58.3 ± 14.6 yrs vs. 64.3 ± 12.0 yrs, p < 0.01) and had a significantly higher logistic EuroSCORE (11.3 ± 10.3% vs. 6.1 ± 8.3%, p < 0.01). Mean ARD was 39.5 ± 7.1 mm in ARR vs. 34.5 ± 5.4 mm in AVR (p < 0.01). In the AVR group, 32.2% of patients had an ARD ≥ 40 mm (n = 59), from these, 8.2% (n = 15) had an ARD ≥ 45 mm prior to the procedure. Procedural times were significantly longer in ARR (Bypass time: 110.3 ± 36.2 mins in ARR vs. 78.2 ± 31.0 mins in AVR, p < 0.01), in 8.2% of AVR patients (n = 15) concomitant aortoplasty was performed. Perioperative complications were similar after both procedures, as stroke occurred in 1.7% (n = 1) after ARR and 2.2% (n = 4) after AVR (p = 1.0), dialysis was not necessary in any ARR patient and in 1.1% (n = 2) in AVR (p = 1.0). In ARR, survival at 30 days was 100% vs. 99.5% in AVR (p = 1.0). Median follow-up was 6.1 years. Survival at 5 years was 91.7% in ARR vs. 82.9% in AVR (p = 0.88). During the observational period, 3.4% (n = 2) of the AVR group needed repeat surgery on the ascending aorta due to an increase in ARD. Conclusion: Our experience shows, that one-third of patients receiving AVR for BAV is not treated according to current guidelines. Re-operations in this group were due to pre-existent RD. However, ARR does not increase perioperative risk and therefore we recommend ARR as the appropriate treatment in patients with pre-existent RD.